Production of Potassium Hydroxide by Conversion – Extraction Method Based on Local Materials - Ro‘ziyeva Farangiz; Elmurodova Hayitgul; Toshpulatov Komiljon; Navruzova Tursunoy; Nurmamatova Cho‘lponoy (Global Scientific Publishing, 2023)
The aim of the work was to study and develop a technological process for obtaining potassium hydroxide by conversion – extraction method based on local materials. Optimal technological parameters of the process have been established. A number of physico-chemical properties of the resulting product have been investigated depending on the technological parameters. The stages of the basic technological scheme for the production of potassium hydroxide based on lime milk and potash are recommended.
Keywords: lime milk; potassium carbonate